Numerical Study of Coupled Electrical-Thermal-Mechanical-Wear Behavior in Electrical Contacts - Fei Shen; Liao-Liang Ke (Metals, 2021)
Electrical contacts involve complicated electrical, thermal, and mechanical phenomena. Fretting wear as a surface damage mechanism significantly weakens the performance of electrical contact components. In this study, a numerical approach is developed to investigate the electrical-thermal-mechanical-wear coupling behavior of electrical contacts. An electrical contact conductance law is used with the current conservation model to evaluate the electrical behavior. A transient heat transfer model, including the Joule heating behavior and a thermal contact conductance law, is employed to calculate the temperature field. Both contact conductance laws are related to the contact pressure distribution obtained by the contact stress analysis. Based on the predicted contact stress and relative slip on contact surfaces, the energy wear model is used to study the evolution of fretting wear depth and contact surface geometry. The material properties in these models are temperature-dependent. The proposed numerical approach is implemented in a finite element modeling of electrical contacts, which is validated by comparing the predicted and experimental results of the wear scar profile. The effects of the fretting wear on the electric potential, current density, contact resistance, temperature, and contact pressure are numerically studied.